Does prosody contribute to the expression of the dialogism of the utterance? First steps based on the analysis of a political interview in French - Nowakowska, Alexandra (Bergen Language and Linguistics Studies, 2023)
Within the framework of utterance production theories “à la française”, different approaches of enunciative heterogeneity have been developed since the end of the 1970’s in interaction, re-work, and re-appropriation of notions of polyphony and dialogism borrowed from the Bakhtin Circle. These approaches, beyond their differences, have had little interest in prosodic, vocal and gestural dimensions of the discursive units under study. It is this “omission” which the present article intends to break by analyzing a political interview. We study the way in which the observed syntactic and rhetorical dialogic markers - direct speech, cleft sentence and pseudo-cleft sentence, negation, parallelism, echo and autonymous modalization - are or are not marked prosodically and vocally.